Controllable Morphology and Structure of MoO3 Hexagonal Poles and Nanobelts - Zhao, Qingchun; Cao, Tian (Asian Journal of Chemistry, 2013)
Various morphology and structure of MoO3 were prepared via hydrothermal reaction method. The experimental results show that Na+ and H+ play a decisive role in the formation of h-MoO3 and a-MoO3. As mol ratio of Na2MoO4 : H2SO4 = 1 : 2 and 1, a-MoO3 nanobelts and h-MoO3 hexagonal poles were obtained, respectively. Scanning electron microscopy and transmission electron microscopy images of the products clearly show that MoO3 possesses a nanobelt and hexagonal pole structure. Electron diffraction patterns of MoO3 nanobelt and hexagonal pole, Raman spectra and X-ray diffraction analysis were used to examine the crystal structure of the obtained products. The obtained nanobelts are pure-phase orthorhombic a-MoO3 nanobelts and hexagonal poles are pure-phase metastable phase of hexagonal h-MoO3.